Ankylosing Spondyloarthritis Resulting Severe Aortic Insufficiency and Aortitis: Exacerbation of Ankylosing Spondyloarthritis and Stenosis of the Main Left Coronary Artery after Mechanical Aortic Valve Implantation with Cardiopulmonary Bypass - Agnė Balčiūnaitė; Algimantas Budrikis; Eglė Rumbinaitė; Jurgita Sabaliauskienė; Vaiva Patamsytė; Vaiva Lesauskaitė (Case Reports in Rheumatology)
Ankylosing spondyloarthritis (AS) is a chronic inflammatory rheumatic disease, strongly related to human leukocyte antigen (HLA)-B27. Cardiac involvement in AS manifests in 2 to 10% of patients as aortic insufficiency, aortitis, mitral valve fibrosis, or disturbance in the conduction of the heart. In this article, we present a case of a 49-year-old male patient with AS, who was referred to our medical institution for elective aortic valve surgery because of severe aortic regurgitation. The histological findings revealed fibrosing endocarditis of aortic valve and nonspecific aortitis of aortic root. Late postoperatively, we observed exacerbation of AS and narrowing of the main left coronary artery (LAD). Our case highlights the importance of proper treatment of AS before and after cardiac surgery. Furthermore, in this case, we suspect association between cardiopulmonary bypass, activity of AS, and coronary artery disease.